Factors of functioning and development of information technologies in the national economy - Karpiak, Anastasiya (Видавництво Львівської політехніки, 2017)
The development of the IT industry in Ukraine today is one of the most important prerequisites for the integration of the state into the European and world civilized community. With a sufficiently rich heritage of highly skilled scientists and engineers, Ukraine has managed to achieve good indicators of the level of development of the IT industry. The result of the study was a dynamic analysis of the level of development and the growth potential of Ukrainian society's informatization in international.
Keywords: national economy; types of economic activity; Information Technology; IT market; IT industry